2011
DOI: 10.1074/jbc.m111.228817
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hepatic Eukaryotic Initiation Factor 2α (eIF2α) Endoplasmic Reticulum (ER) Stress Response Pathway on Insulin-mediated ER Stress and Hepatic and Peripheral Glucose Metabolism

Abstract: Recent studies have implicated endoplasmic reticulum (ER) stress in insulin resistance associated with caloric excess. In mice placed on a 3-day high fat diet, we find augmented eIF2α signaling, together with hepatic lipid accumulation and insulin resistance. To clarify the role of the liver ER stress-dependent phospho-eIF2α (eIF2α-P) pathway in response to acute caloric excess on liver and muscle glucose and lipid metabolism, we studied transgenic mice in which the hepatic ER stress-dependent eIF2α-P pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 31 publications
4
50
0
1
Order By: Relevance
“…In support of findings in animals [7,19,21,23,24] and humans [25,30,31], our data show that an HFD rapidly impairs the ability of insulin to suppress hepatic glucose output, with peripheral insulin resistance developing subsequently. Furthermore, our data suggest that the liver quantitatively has the most significant impact on postprandial glycaemia, as both peak glucose intolerance and hepatic insulin resistance occurred within 3-7 days of HFD, despite the absence of muscle insulin resistance at this time.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In support of findings in animals [7,19,21,23,24] and humans [25,30,31], our data show that an HFD rapidly impairs the ability of insulin to suppress hepatic glucose output, with peripheral insulin resistance developing subsequently. Furthermore, our data suggest that the liver quantitatively has the most significant impact on postprandial glycaemia, as both peak glucose intolerance and hepatic insulin resistance occurred within 3-7 days of HFD, despite the absence of muscle insulin resistance at this time.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, consistent with our hypothesis, we show that an increase in lipid metabolites are associated with defects in tissue insulin action, suggesting that lipotoxicity is a generalised mechanism associated with the induction of insulin resistance in individual tissues of mice. Studies in rodents [7,[19][20][21]23], dogs [24] and humans [25][26][27], have shown that short-term exposure to HFD/overfeeding (3-28 days) results in the rapid development of insulin resistance and glucose intolerance. Often these changes occur with only modest increases in fat mass, highlighting that metabolic defects occur prior to the onset of obesity and do not require extensive periods of fat feeding.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mice with high fat feeding not only develop hepatic steatosis, insulin resistance, and type 2 diabetes, but also exhibit ER stress markers in liver and other tissues. [15][16][17] Thus, ER stress and hepatic steatosis can form a positive feedback loop to further amplify liver inflammation and injury. Here, we show that mRNA levels of 2 ER stress- induced genes, namely Ddit3 and Asns, were significantly increased from d 2 of colchicine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] We therefore monitored in colchicine-treated and nontreated fish the expression of 2 ER stress-induced genes, Ddit3/Chop (DNA-damage inducible transcript 3) and Asns (asparagine synthetase). As shown in Figure 8A, the mRNA levels of these genes were significantly increased from d 2 of colchicine treatment, supporting the induction of an ER-stress in this condition.…”
Section: Colchicine Treatment Induces Er Stress Markers As Well As Aumentioning
confidence: 99%
“…In this setting, insulin still increased hepatic Grp78 protein expression as well as X-box binding protein 1 (XBP1s) and C/EBP homologous protein (CHOP) mRNA expression, while other functions of insulin, such as suppression of hepatic glucose output, were decreased (2,6). Moreover, in mice functionally lacking the eIF2a-mediated branch of the unfolded protein response (7), the increase in XBP1s and CHOP by insulin was further enhanced, demonstrating that the eIF2a-mediated arm of the unfolded protein response is needed to properly resolve insulinmediated ER stress (2,8). It would be important to understand whether or not insulin-resistant humans also remain sensitive to insulin-induced ER stress.…”
mentioning
confidence: 99%